Studying the motor rhythm of some pommel horse skills using qualitative and video analysis as the basis for developing performance level of players in training center of the Saudi Arabia Gymnastics Federation - Abd El-Rahman, A. A. M.; Ahmed, M. M. A. (World Journal of Sport Sciences, 2010)
This research aims to identify faults in motor performance of anchoring on both hands of the investigated motor skills on the pommel horse apparatus for junior gymnastics under ten years in the training center of the Saudi Arabia Gymnastics Federation in Riyadh using the motor qualitative and video analysis as the basis for developing a training program through the following: To identify faults in performance of the studied skills through the motor qualitative analysis. To identify the impact of the training program to improve components level of physical fitness of the studied skills. To identify the impact of the training program to improve the level of performance of the studied skills. The sample of the research included a sample of eight players represent the research community of junior gymnastics under ten years old from the training center of the Saudi Arabia Gymnastics Federation in Riyadh and registered in the federation. The researchers used the experimental method for conducting this research. The steps of the research were represented as follow: First: qualitative analysis of the studied skills according to Gangstead and Beverides [1]. Second: faults classification Form. Third: Developing the proposed physical and skill exercises specific to the studied skills and associated to motor rhythm. The results indicated the following: There are significant differences between pre and post measurements of the research sample in the physical level in favor of the post measurement. There are significant differences between pre and post measurements in the performance level of the studied skills (Magyar- Sivado - Thomas American scissor) in favor of the post measurement. Integrating between the prepared physical program and the skill program is considered the best way to develop perform skills accurately in the least time possible. Developing the motor rhythm of motor the studied skills and for gymnastics in general helps to develop and link between the motor skills.